Political time in public bureaucracies: Explaining variation of structural duration in European governments - Julia Fleischer; Philippe Bezes; Kutsal Yesilkagit (Public Administration Review, 2023)
Structural duration conveys stability but also resilience in central government and is therefore a key issue in the debate on the structure and organization of government. This paper discusses three core variants of structural duration to study the explanatory relevance of politics. We compare these durations across ministerial units in four European democracies (Germany, France, The Netherlands, and Norway) from 1980 to 2013, totaling over 17,0000.167emunits. Our empirical analyses show that cabinets' ideological turnover and extremism are the most significant predictors of all variants of duration, whereas polarization in parliament as well as new prime ministers without office experience yield the predicted significant negative effects for most models. We discuss these findings and avenues for future research that acknowledge the definition and measures for structural change as well as temporal aspects of the empirical phenomenon more explicitly.
Keywords: 340